Application Of The Brute Force Method For Tracing Graduates Of Universitas Dehasen Bengkulu - Vina Silva Anugrah; Khairil Khairil; Abdussalam Al Akbar (Jurnal Media Computer Science, 2026)
The tracer study is one of the essential activities carried out by universities to monitor the success of their graduates in the workforce as well as to serve as an evaluation tool for improving the quality of education. However, the alumni tracking process that is conducted manually often encounters various obstacles, such as difficulties in data searching, information duplication, and delays in reporting. Based on these problems, this study aims to develop an alumni tracking application for Universitas Dehasen Bengkulu by implementing the Brute Force algorithm as a method for searching alumni data based on specific keywords. The implementation results show that the system can display alumni search results quickly and accurately by providing information on the number of string comparisons, execution time, and match percentage. In addition, the application also provides features for alumni data management, alumni questionnaire input, and job information updates, which support the digital implementation of tracer study activities. Thus, the application of the Brute Force algorithm in this system has proven to be effective in assisting the alumni data search process and improving the efficiency and accuracy of graduate tracking at Universitas Dehasen Bengkulu.